Long versus short dual antiplatelet therapy in acute coronary syndrome patients treated with prasugrel or ticagrelor and coronary revascularization: Insights from the RENAMI registry. (May 2020) - D'Ascenzo, Fabrizio; Bertaina, Maurizio; Fioravanti, Francesco; Bongiovanni, Federica; Raposeiras-Roubin, Sergio; Abu-Assi, Emad; Kinnaird, Tim; Ariza-Solé, Albert; Manzano-Fernández, Sergio; Templin, Christian; Velicki, Lazar; Xanthopoulou, Ioanna; et al.
Introduction: The benefits of short versus long-term dual antiplatelet therapy (DAPT) based on the third generation P2Y12 antagonists prasugrel or ticagrelor, in patients with acute coronary syndromes treated with percutaneous coronary intervention remain to be clearly defined due to current evidences limited to patients treated with clopidogrel. Methods: All acute coronary syndrome patients from the REgistry of New Antiplatelets in patients with Myocardial Infarction (RENAMI) undergoing percutaneous coronary intervention and treated with aspirin, prasugrel or ticagrelor were stratified according to DAPT duration, that is, shorter than 12 months (D1 group), 12 months (D2 group) and longer than 12 months (D3 group). The three groups were compared before and after propensity score matching. Net adverse clinical events (NACEs), defined as a combination of major adverse cardiac events (MACEs) and major bleedings (including therefore all cause death, myocardial infarction and Bleeding Academic Research Consortium (BARC) 3–5 bleeding), were the primary end points, MACEs (a composite of all cause death and myocardial infarction) the secondary one. Single components of NACEs were co-secondary end points, along with BARC 2–5 bleeding, cardiovascular death and stent thrombosis. Results: A total of 4424 patients from the RENAMI registry with available data on DAPT duration were included in the model. After propensity score matching, 628 patients from each group were selected. After 20 months of follow up, DAPT for 12 months and DAPT for longer than 12 months significantly reduced the risk of NACE (D1 11.6% vs . D2 6.7% vs . D3 7.2%, p = 0.003) and MACE (10% vs . 6.2% vs . 2.4%, p < 0.001) compared with DAPT for less than 12 months. These differences were driven by a reduced risk of all cause death (7.8% vs . 1.3% vs . 1.6%, p < 0.001), cardiovascular death (5.1% vs . 1.0% vs . 1.2%, p < 0.0001) and recurrent myocardial infarction (8.3% vs . 5.2% vs . 3.5%, p = 0.002). NACEs were lower with longer DAPT despite a higher risk of BARC 2–5 bleedings (4.6% vs . 5.7% vs . 6.2%, p = 0.04) and a trend towards a higher risk of BARC 3–5 bleedings (2.4% vs . 3.3% vs . 3.9%, p = 0.06). These results were not consistent for female patients and those older than 75 years old, due to an increased risk of bleedings which exceeded the reduction in myocardial infarction. Conclusion: In unselected real world acute coronary syndrome patients treated with percutaneous coronary intervention, DAPT with prasugrel or ticagrelor prolonged beyond 12 months markedly reduces fatal and non-fatal ischaemic events, offsetting the increased risk deriving from the higher bleeding risk. On the contrary, patients >75 years old and female ones showed a less favourable risk–benefit ratio for longer DAPT due to excess of bleedings.